2016
DOI: 10.1016/j.jtice.2015.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Metallocene-catalyzed ethylene−α-olefin isomeric copolymerization: A perspective from hydrodynamic boundary layer mass transfer and design of MAO anion

Abstract: Keywords:Metallocene catalyst Pseudo-homogeneous and in-situ heterogeneous isomeric ethylene−α-olefin copolymerization Hydrodynamic boundary layer mass transfer Inter-and intra-chain backbone composition distribution Lamellar thickness distribution Thermal properties a b s t r a c t This study reports a novel conceptual framework that can be easily experimented to evaluate the effects of hydrodynamic boundary layer mass transfer, methylaluminoxane (MAO) anion design, and comonomer steric hindrance on metalloce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 77 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…Such complexes are intermediates of the chain release via Zr-Al transfer [86][87][88]. At the same time, the practice of using high Al MAO /Zr ratios in the laboratory was due to lthe ow effectiveness of MAO as an alkylation agent; the Al MAO /Zr ratios of 10 2 MAO were found to be insufficient for the activation of bis-indenyl and bis-fluorenyl complexes [89]. In 2017, Nifant'ev et al proposed a two-stage activation method for a wide array of LZrCl 2 complexes.…”
Section: Metallocene-catalyzed Oligomerization Of -Olefins and Activamentioning
confidence: 99%
“…Such complexes are intermediates of the chain release via Zr-Al transfer [86][87][88]. At the same time, the practice of using high Al MAO /Zr ratios in the laboratory was due to lthe ow effectiveness of MAO as an alkylation agent; the Al MAO /Zr ratios of 10 2 MAO were found to be insufficient for the activation of bis-indenyl and bis-fluorenyl complexes [89]. In 2017, Nifant'ev et al proposed a two-stage activation method for a wide array of LZrCl 2 complexes.…”
Section: Metallocene-catalyzed Oligomerization Of -Olefins and Activamentioning
confidence: 99%
“…The melting temperatures ( T m ) at each point can thus be related to the equivalent dimensions of that crystal lamella (crystallite) by using Flory and GT equations, also termed as MGT equation, given by Equation Tm=Tmotrue(12σssfeΔHfoLfclamellatrue) where Tmo (equilibrium melting temperature of perfect crystal of ethylene homopolymer) = 418.65 K; ΔHfo (heat of fusion per unit volume for the perfect crystal) = 290 J cm −3 ; L fclamella is the folded crystal lamellar thickness, and σ ssfe (crystallite specific surface free energy) = 90 mJ · m −2 . However, for the Tmo for the copolymer (Tm,copolymo) Equation is used .…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the lamellar thickness of the homopolymer is much more widely distributed than the copolymers; with a high weight average lamellar thickness (WALT) calculated using Flory and GT equations. This could be ascribed to the resulting decrease in longer lamellae by the butyl branching of the copolymer …”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, NMR spectroscopy is one of the most important analytical tools that has been used in several fields. These fields include structural biology [29][30][31][32][33][34][35][36][37][38], organic chemistry [39][40][41][42][43][44][45][46][47][48][49][50][51][52], polymer characterization [40,46,[53][54][55][56][57][58][59][60][61][62][63][64], inorganic chemistry [65][66][67][68][69][70][71][72][73][74][75], and physics [76][77][...…”
mentioning
confidence: 99%